MEMBERDAYAKAN MOTIVASI BELAJAR DAN KETERAMPILAN BERPIKIR KRITIS SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN DISCOVERY PADA MATERI GETARA DAN GELOMBANG - Sholikhan, Sholikhan; Amul, Tilde Novaria; Ain, Nurul (Transpublika Publisher, 2023)
The objective of this research is (1) to determine the quality of implementing the Discovery Learning model that can enhance students' learning motivation and critical thinking, (2) to assess the improvement in students' critical thinking skills through the application of the Discovery Learning model, and (3) to identify the enhancement in students' learning motivation through the implementation of the Discovery Learning model. The research method employed in this study is classroom action research (CAR), consisting of the stages of planning, action, observation, and reflection. The research subjects are 37 eighth-grade students at SMP PGRI 02 Singosari in the academic year 2022/2023. Data collection procedures include tests, observations, and documentary studies. The research findings indicate that: (1) the quality of implementing the Discovery Learning model, which enhances critical thinking skills and learning motivation, is considered good; (2) there is an improvement in students' critical thinking skills through the application of the Discovery Learning model, (3) there is an increase in students' learning motivation through the implementation of the Discovery Learning model.